RANCANG BANGUN SISTEM PROTEKSI DAN MONITORING ARUS DAN TEGANGAN LEBIH BERBASIS TELEGRAM - Nursalim Nursalim; Wellem F. Galla; Sudirman Syam; Sri Kurniati A (Jurnal Media Elektro, 2022)
The electrical protection system is designed with the aim of preventing or reducing damage due to interference on equipment that is traversed by short circuit currents, in addition, with a protection system, the undisturbed area can be minimized as small as possible. In a house, a Miniature Circuit Breaker (MCB) is usually used as a means of protection to break the short circuit current that occurs. However, an MCB has limitations including it cannot be controlled from a certain distance, so if the MCB is to reconnect after it has worked, the user must raise the lever manually. The purpose of this research is to make an electrical protection device for household use that can be controlled and monitored remotely. This system is built using the esp module. 8266, pzem-004t sensor and solid state relay by utilizing the telegram application as control and notification. The test results show that the values ​​of current and voltage as well as electrical power can be displayed by smartphone users via the telegram application by using certain commands according to what has been programmed.